Implementation Of Contextual Teaching And Learning Learning Model To Improve Pkn Learning Outcomes In Elementary Schools - Isti Septianing; Juliana Khoirotun Nisa; Siska Dewi Rahmawati; Endrise Septina Rawanoko (KOLABORASI: Journal of Multidisciplinary, 2024)
Learning is an interactive process that involves collaboration between students, teachers, and the surrounding environment. Learning models have an important role in achieving optimal learning outcomes. One of the learning models that can be applied is Contextual Teaching and Learning (CTL). This study aims to conduct a literature review of the influence of the Contextual Teaching and Learning learning model on elementary school civics learning outcomes. The method used in this study is the SLR (Systematic Literature Review) method. Data collection was carried out by collecting and reviewing articles related to Contextual Teaching and Learning published from 2014-2024. The articles used in this study are 12 journal articles obtained from the Google Scholar database. Based on this study, the use of the Contextual Teaching and Learning learning model has an influence on improving the learning outcomes of Pkn in elementary schools.